2014
DOI: 10.5414/cn108138
|View full text |Cite
|
Sign up to set email alerts
|

The association of endothelial nitric oxide synthase gene G894T polymorphism and serum nitric oxide concentration with microalbuminuria in patients with gestational diabetes

Abstract: The G894T polymorphism of eNOS gene and decreased NO concentration seem to be independent predictors of increased urinary excretion of albumin in patients with GDM. Determining the frequency of eNOS gene G894T polymorphism may help to identify pregnancies at increased risk of microalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…All of these correlations were positive with ADMA and negative with NO. Similarly Atay et al (37) found NO, glucose, creatinine, and microalbuminuria were significantly different between GDM patients and control subjects and in another study, Atay et al (38) found normotensive patients with GDM had significantly reduced NO levels. Moreover, Gumus et al (39) found the insulin and ADMA, and HOMA-IR levels were significantly higher in patients with a history of GDM and Xia et al (40) detected significantly higher serum ADMA and CRP with increased carotid intima-media thickness (CIMT) in women with previous GDM than healthy controls with positive correlation between ADMA and CRP and CIMT with ADMA being a significant predictor for elevated CIMT in subjects with previous GDM.…”
Section: Discussion:-mentioning
confidence: 84%
“…All of these correlations were positive with ADMA and negative with NO. Similarly Atay et al (37) found NO, glucose, creatinine, and microalbuminuria were significantly different between GDM patients and control subjects and in another study, Atay et al (38) found normotensive patients with GDM had significantly reduced NO levels. Moreover, Gumus et al (39) found the insulin and ADMA, and HOMA-IR levels were significantly higher in patients with a history of GDM and Xia et al (40) detected significantly higher serum ADMA and CRP with increased carotid intima-media thickness (CIMT) in women with previous GDM than healthy controls with positive correlation between ADMA and CRP and CIMT with ADMA being a significant predictor for elevated CIMT in subjects with previous GDM.…”
Section: Discussion:-mentioning
confidence: 84%
“…Three comparisons (Motawi et al ,10 Atay e t al 19 and Sakar et al 21) were identified as the main contributors to the heterogeneity by using Galbraith plot. The MD value and 95% CI (MD −0.13 μmol/L, 95% CI −0.22 to −0.04 μmol/L, p heterogeneity =0.89, p MD <0.001) did not change substantially after excluding these outlier comparisons (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…NOS3 gene polymorphisms were also investigated in pregnant women with GDM. Atay et al . investigated the association between the NOS3 gene rs1799983 polymorphism and serum nitric oxide levels and microalbuminuria in women with GDM and healthy pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…33 NOS3 gene polymorphisms were also investigated in pregnant women with GDM. Atay et al 34 investigated the association between the NOS3 gene rs1799983 poly- Cycloogenase 2 is the enzyme responsible for the synthesis of prostaglandins. It was shown that this enzyme may be involved in the pathogenesis of diabetes type 2 and GDM.…”
Section: Discussionmentioning
confidence: 99%